Hierarchical pore ZSM-11 molecular sieve and preparation method thereof, molecular sieve catalyst and preparation method and application thereof
By preparing multi-stage pore ZSM-11 molecular sieve and loading transition metal oxides, the problem of restricted diffusion path of traditional microporous molecular sieve is solved, and the efficient degradation performance of acetaminophen is achieved.
Patent Information
- Application Number
- CN202411476732.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-25
AI Technical Summary
The pore size of traditional microporous molecular sieve is below 2 nm, which limits the diffusion and transport of reactants and degradation intermediates, affects the performance of the catalyst, and is difficult to effectively remove the residual acetaminophen in the water.
The preparation method of multi-stage pore ZSM-11 molecular sieve is adopted. Through dynamic crystallization, calcination and ion exchange steps, a molecular sieve with a larger specific surface area and a multi-stage pore structure is formed, and the transition metal oxide is supported to improve the catalytic performance.
The diffusion path is significantly shortened, diffusion mass transfer is enhanced, the dispersion of metal active components and the palpability and utilization of active sites are improved, and the degradation performance of acetaminophen is improved.
Smart Images

Figure CN119503830A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic degradation, and specifically relates to a multi-level pore ZSM-11 molecular sieve and a preparation method thereof, a molecular sieve catalyst and a preparation method and application thereof. Background Art
[0002] As a typical non-steroidal anti-inflammatory drug, acetaminophen not only relieves pain for humans, but also enters natural water bodies during the production and use process. Due to the characteristics of acetaminophen such as easy enrichment in water bodies, strong tolerance, and difficulty in biodegradation, it is difficult to be effectively removed by traditional water treatment technologies, posing a serious threat to ecological balance and human drinking water safety. Removing residual acetaminophen in water bodies is an environmental problem that needs to be solved urgently. Therefore, exploring a method for efficiently removing acetaminophen is crucial to maintaining ecological balance and protecting human health. In recent years, advanced oxidation technology based on transition metal activation of persulfate to produce reactive oxygen species has attracted much attention in the degradation of organic pollutants.
[0003] Studies have shown that due to Co 3+ / Co 2+ Cobalt (Co) is considered to be the best transition metal for activating persulfate due to its high standard redox potential (1.92V). Co species are usually loaded on various carbon material carriers such as graphene, carbon nanotubes and porous carbon derived from metal organic framework materials. However, these carbon materials generally have disadvantages such as complex production process, high synthesis cost and low mechanical strength, which greatly limit their practical application in the field of advanced oxidation technology. Therefore, exploring new carrier materials to improve the feasibility of catalysts in practical applications is a hot and difficult topic in this field. Molecular sieve is an inorganic crystalline material with a regular pore structure. It has the advantages of large specific surface area, easily adjustable elemental composition, easily modified surface functional groups, adjustable pore size, good hydrothermal stability, high mechanical strength and green environmental protection. It is one of the ideal carrier materials in the field of advanced oxidation technology. Among them, ZSM-11 molecular sieve (MEL topology structure) has a two-dimensional ten-membered ring pore structure with two straight pores. They are parallel to the a-axis and the b-axis respectively, and cross each other perpendicularly to form two sizes. The straight pores and large-sized cross cavities of ZSM-11 molecular sieve are conducive to the adsorption of organic degradation intermediates and improve the catalytic degradation effect. To this end, the present invention uses ZSM-11 molecular sieve as a carrier material.
[0004] However, the pore size of traditional microporous molecular sieves is below 2 nm, which severely limits the diffusion and transport of reactants and degradation intermediates, affecting the performance of the catalyst. Summary of the invention
[0005] The purpose of the present invention is to provide a multi-level pore ZSM-11 molecular sieve and a preparation method thereof, a molecular sieve catalyst and a preparation method and application thereof. The molecular sieve provided by the present invention can greatly shorten the diffusion path and enhance diffusion mass transfer. At the same time, the larger specific surface area created is conducive to the dispersion of metal active components and improves the accessibility and utilization rate of active sites.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a multi-level pore ZSM-11 molecular sieve, comprising the following steps:
[0008] first mixing tetrabutylammonium hydroxide solution, sodium hydroxide, silica sol and water to obtain a gel system;
[0009] The gel system is subjected to dynamic crystallization and first calcination in sequence to obtain a parent ZSM-11 molecular sieve;
[0010] The parent ZSM-11 molecular sieve and the tetrabutylammonium hydroxide solution are mixed for the second time to obtain a dispersed system;
[0011] The dispersed system is sequentially subjected to static crystallization and secondary calcination to obtain a primary ZSM-11 molecular sieve;
[0012] The primary ZSM-11 molecular sieve is placed in an ammonium chloride solution for ion exchange and then subjected to a third calcination to obtain the multi-level pore ZSM-11 molecular sieve.
[0013] Preferably, in the first mixing, the mass concentration of the tetrabutylammonium hydroxide solution is 10-25%;
[0014] The solid content of the silica sol is 25-40%;
[0015] The molar ratio of tetrabutylammonium hydroxide in the tetrabutylammonium hydroxide solution, silicon dioxide in the silica sol, water and sodium hydroxide is 4.5-18:60-180:810-2250:9-18;
[0016] The first mixing is performed under stirring conditions, the stirring temperature is room temperature, and the time is 18 to 30 hours.
[0017] Preferably, the dynamic crystallization is carried out under rotation, and the rotation speed is 10 to 20 rpm.
[0018] The dynamic crystallization includes sequentially performing first stage crystallization, second stage crystallization and third stage crystallization;
[0019] The temperature of the first stage crystallization is 70-90°C and the time is 36-72h;
[0020] The temperature of the second stage crystallization is 110-130°C and the time is 36-72h;
[0021] The temperature of the third stage crystallization is 150-170°C and the time is 20-36h;
[0022] The temperature of the first calcination is 570-600° C., and the heat preservation time is 12-18 hours.
[0023] Preferably, in the second mixing, the concentration of the tetrabutylammonium hydroxide solution is 0.40 to 1.4 mol / L;
[0024] The dosage ratio of the parent ZSM-11 molecular sieve and the tetrabutylammonium hydroxide solution is 1g: 10-25mL;
[0025] The second mixing is performed under stirring conditions, and the stirring time is 30 to 120 minutes.
[0026] Preferably, the static crystallization temperature is 150-180°C and the time is 36-72h;
[0027] The second calcination temperature is 570-600°C, and the holding time is 12-18h;
[0028] The ion exchange temperature is 60-80°C, the time is 8-12h, and it is repeated 3 times;
[0029] The temperature of the third calcination is 570-600° C., and the heat preservation time is 6-12 hours.
[0030] The present invention also provides a multi-level pore ZSM-11 molecular sieve prepared by the preparation method described in the above technical solution.
[0031] The present invention also provides a molecular sieve catalyst, comprising a multi-level pore ZSM-11 molecular sieve and a transition metal oxide supported on the multi-level pore ZSM-11 molecular sieve;
[0032] The multi-level pore ZSM-11 molecular sieve is the multi-level pore ZSM-11 molecular sieve described in the above technical solution;
[0033] The transition metal oxide includes Co 3 O 4 , Fe 3 O 4 , Mn 3 O 4 or CuO.
[0034] Preferably, the loading mass percentage of the transition metal oxide is 10-15%;
[0035] The average particle size of the transition metal oxide is 2 to 3.5 nm.
[0036] The present invention also provides a method for preparing the molecular sieve catalyst described in the above technical solution, comprising the following steps:
[0037] Mixing polyvinyl alcohol, a transition metal salt and water to obtain a metal salt solution; the transition metal salt includes a cobalt salt, an iron salt, a manganese salt or a copper salt;
[0038] Mixing the multi-level pore ZSM-11 molecular sieve and water to obtain a molecular sieve liquid;
[0039] Under stirring conditions, the molecular sieve material liquid is dropped into the metal salt solution, and after continuing to stir, calcination is performed to obtain the molecular sieve catalyst.
[0040] The present invention also provides the use of the molecular sieve catalyst described in the above technical solution or the molecular sieve catalyst prepared by the preparation method described in the above technical solution in catalytic degradation of non-steroidal drugs or antibiotics.
[0041] The present invention provides a method for preparing a multi-level pore ZSM-11 molecular sieve, comprising the following steps: first mixing a tetrabutylammonium hydroxide solution, sodium hydroxide, silica sol and water to obtain a gel system; performing dynamic crystallization and a first calcination on the gel system in sequence to obtain a parent ZSM-11 molecular sieve; second mixing the parent ZSM-11 molecular sieve and a tetrabutylammonium hydroxide solution to obtain a dispersed system; performing static crystallization and a second calcination on the dispersed system in sequence to obtain a primary ZSM-11 molecular sieve; placing the primary ZSM-11 molecular sieve in an ammonium chloride solution for ion exchange, and then performing a third calcination to obtain the multi-level pore ZSM-11 molecular sieve. The present invention adopts a "dissolution-recrystallization" method to synthesize a multi-level pore ZSM-11 molecular sieve, which can greatly shorten the diffusion path, strengthen diffusion mass transfer, and at the same time create a larger specific surface area that is conducive to the dispersion of metal active components and improves the accessibility and utilization of active sites.
[0042] The present invention also provides a method for preparing a molecular sieve catalyst, comprising the following steps: mixing polyvinyl alcohol (PVA), a transition metal salt and water to obtain a metal salt solution; mixing a multi-level pore ZSM-11 molecular sieve and water to obtain a molecular sieve feed solution; dripping the molecular sieve feed solution into the metal salt solution under stirring, continuing to stir, and then calcining to obtain the molecular sieve catalyst. The present invention uses a PVA-assisted impregnation method to introduce transition metal species, and the innovation lies in: (1) the cross-linked structure of the PVA molecules is intended to provide a confined environment for the transition metal species to prevent them from agglomerating and growing; (2) the PVA molecules are rich in a large number of hydroxyl groups, which are easy to hydrogen bond with the silanol groups on the surface of the molecular sieve, and the transition metal species can be introduced into the molecular sieve in a directional manner, thereby improving the accessibility of the metal active sites.
[0043] The multi-level pore structure of the molecular sieve catalyst provided by the present invention and the uniform dispersion of transition metal oxides on the catalyst significantly improve the accessibility of metal active sites and maximize the performance of activating persulfate to degrade non-steroidal drugs or antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 is the XRD pattern of the molecular sieve catalyst obtained in Example 1;
[0045] Figure 2 FT-IR image of the molecular sieve catalyst obtained in Example 1;
[0046] Figure 3 TEM image of the molecular sieve catalyst obtained in Example 1;
[0047] Figure 4 N is the molecular sieve catalyst obtained in Example 1 2 Adsorption-desorption isotherms;
[0048] Figure 5 is the pore size distribution curve of the molecular sieve catalyst obtained in Example 1;
[0049] Figure 6 The XPS spectra of the molecular sieve catalysts obtained in the examples and comparative examples are shown;
[0050] Figure 7 The Co 2p high-resolution XPS fine spectra of the molecular sieve catalysts obtained in Examples and Comparative Examples;
[0051] Figure 8 The catalytic reaction degradation effect diagram of the molecular sieve catalyst obtained in the examples and comparative examples;
[0052] Fig. 9 The catalytic reaction degradation effect diagram of the molecular sieve catalyst of Example 1 at different addition amounts;
[0053] Fig.10 The effect diagram of the molecular sieve catalyst of Example 1 on the degradation of acetaminophen of different concentrations;
[0054] Fig.11 The figure is a diagram showing the degradation effect of the molecular sieve catalyst of Example 1 on acetaminophen solutions with different pH values;
[0055] Fig.12 The figure is a diagram showing the degradation effect of the molecular sieve catalyst of Example 1 on acetaminophen solutions containing different anions and cations;
[0056] Fig.13 This is a diagram showing the degradation effect of the molecular sieve catalyst obtained in Example 1 on antibiotics;
[0057] Fig.14 This is the TEM image of the molecular sieve catalyst obtained in Comparative Example 1. DETAILED DESCRIPTION
[0058] The present invention provides a method for preparing a multi-level pore ZSM-11 molecular sieve, comprising the following steps:
[0059] first mixing tetrabutylammonium hydroxide solution, sodium hydroxide, silica sol and water to obtain a gel system;
[0060] The gel system is subjected to dynamic crystallization and first calcination in sequence to obtain a parent ZSM-11 molecular sieve;
[0061] The parent ZSM-11 molecular sieve and the tetrabutylammonium hydroxide solution are mixed for the second time to obtain a dispersed system;
[0062] The dispersed system is sequentially subjected to static crystallization and secondary calcination to obtain a primary ZSM-11 molecular sieve;
[0063] The primary ZSM-11 molecular sieve is placed in an ammonium chloride solution for ion exchange and then subjected to a third calcination to obtain the multi-level pore ZSM-11 molecular sieve.
[0064] The present invention first mixes tetrabutylammonium hydroxide solution, sodium hydroxide, silica sol and water to obtain a gel system.
[0065] In the present invention, the water is preferably deionized water. In the present invention, the mass concentration of the tetrabutylammonium hydroxide solution is preferably 10-25%; and the solid content of the silica sol is preferably 25-40%.
[0066] In the present invention, the molar ratio of tetrabutylammonium hydroxide in the tetrabutylammonium hydroxide solution, silicon dioxide in the silica sol, water and sodium hydroxide is preferably 4.5-18:60-180:810-2250:9-18, and specifically can be 9:90:1065:12.897. In the present invention, the first mixing is preferably carried out under stirring, the stirring temperature is preferably room temperature, the time is preferably 18-30 hours, and more preferably 24 hours.
[0067] In the present invention, the first mixing process is preferably: adding tetrabutylammonium hydroxide solution and sodium hydroxide into water and stirring, and then adding silica sol; the stirring time is preferably 15 minutes.
[0068] After obtaining the gel system, the present invention sequentially performs dynamic crystallization and first calcination on the gel system to obtain a parent ZSM-11 molecular sieve.
[0069] In the present invention, the dynamic crystallization is preferably carried out under the condition of rotation, and the number of revolutions is preferably 10-20rpm, and more preferably 15rpm. In the present invention, the dynamic crystallization preferably includes the first stage crystallization, the second stage crystallization and the third stage crystallization in sequence; the temperature of the first stage crystallization is preferably 70-90°C, specifically 70°C, 75°C, 80°C, 85°C or 90°C; the time is preferably 36-72h, specifically 36h, 48h, 60h or 72h; the temperature of the second stage crystallization is preferably 110-130°C, specifically 110°C, 120°C or 130°C; the time is preferably 36-72h, specifically 36h, 48h, 60h or 72h; the temperature of the third stage crystallization is preferably 150-170°C, specifically 150°C, 160°C, 165°C or 170°C; the time is preferably 20-36h, specifically 20h, 24h, 30h or 36h.
[0070] After the dynamic crystallization, the present invention also preferably includes centrifuging the obtained system and drying the separated solid; the rotation speed of the centrifugal separation is preferably 5000 rpm.
[0071] In the present invention, the temperature of the first calcination is preferably 570-600° C., and the holding time is preferably 12-18 hours. In the present invention, the template agent can be removed by the first calcination to obtain the parent ZSM-11 molecular sieve.
[0072] After obtaining the parent ZSM-11 molecular sieve, the present invention performs a second mixing of the parent ZSM-11 molecular sieve and a tetrabutylammonium hydroxide solution to obtain a dispersed system.
[0073] In the present invention, the concentration of the tetrabutylammonium hydroxide solution is preferably 0.40-1.4 mol / L, specifically 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.2 mol / L or 1.4 mol / L; the dosage ratio of the parent ZSM-11 molecular sieve and the tetrabutylammonium hydroxide solution is preferably 1 g: 10-25 mL; the second mixing is preferably carried out under stirring, and the stirring time is preferably 30-120 min.
[0074] After obtaining the dispersed system, the present invention sequentially performs static crystallization and secondary calcination on the dispersed system to obtain a primary ZSM-11 molecular sieve.
[0075] In the present invention, the temperature of the static crystallization is preferably 150-180°C, specifically 150°C, 160°C, 165°C, 170°C, 175°C or 180°C; the time is preferably 36-72h, specifically 36h, 48h, 60h or 72h. After the static crystallization, the present invention also preferably includes centrifuging the obtained system and drying the separated solid; the rotation speed of the centrifugal separation is preferably 5000rpm.
[0076] In the present invention, the temperature of the second calcination is preferably 570-600° C., and the holding time is preferably 12-18 hours. In the present invention, the template can be removed by the second calcination to obtain a primary ZSM-11 molecular sieve.
[0077] After obtaining the primary ZSM-11 molecular sieve, the present invention places the primary ZSM-11 molecular sieve in an ammonium chloride solution for ion exchange, and then performs a third calcination to obtain the multi-level pore ZSM-11 molecular sieve.
[0078] In the present invention, the concentration of the ammonium chloride solution is preferably 0.5-1 mol / L. In the present invention, the dosage ratio of the primary ZSM-11 molecular sieve and the ammonium chloride solution is preferably 1g:30-50mL, specifically 1g:30mL, 1g:40mL or 1g:50mL. In the present invention, the temperature of the ion exchange is preferably 60-80°C, the time is preferably 8-12h, and it is preferably repeated 3 times. In the present invention, the temperature of the third calcination is preferably 570-600°C, and the insulation time is preferably 6-12h.
[0079] The present invention also provides a multi-level pore ZSM-11 molecular sieve prepared by the preparation method described in the above technical solution. In the present invention, the specific surface area of the multi-level pore ZSM-11 molecular sieve is preferably 260 to 320 m 2 ·g -1In the present invention, the micropore size of the multi-level pore ZSM-11 molecular sieve is preferably 0.53×0.54 nm, wherein 0.53×0.54 nm represents the inner diameter size of the elliptical straight pores of the ZSM-11 molecular sieve in two perpendicular directions; the mesopore size is preferably concentrated at 11 nm.
[0080] The present invention also provides a molecular sieve catalyst, comprising a multi-level pore ZSM-11 molecular sieve and a transition metal oxide supported on the multi-level pore ZSM-11 molecular sieve;
[0081] The multi-level pore ZSM-11 molecular sieve is the multi-level pore ZSM-11 molecular sieve described in the above technical solution;
[0082] The transition metal oxide includes Co 3 O 4 , Fe 3 O 4 , Mn 3 O 4 or CuO.
[0083] In the present invention, the loading mass percentage of the transition metal oxide is preferably 10-15%; the average particle size of the transition metal oxide is preferably 2-3.5 nm.
[0084] The present invention also provides a method for preparing the molecular sieve catalyst described in the above technical solution, comprising the following steps:
[0085] Mixing polyvinyl alcohol, a transition metal salt and water to obtain a metal salt solution; the transition metal salt includes a cobalt salt, an iron salt, a manganese salt or a copper salt;
[0086] Mixing the multi-level pore ZSM-11 molecular sieve and water to obtain a molecular sieve liquid;
[0087] Under stirring conditions, the molecular sieve material liquid is dropped into the metal salt solution, and after continuing to stir, calcination is performed to obtain the molecular sieve catalyst.
[0088] The invention mixes polyvinyl alcohol, transition metal salt and water to obtain a metal salt solution.
[0089] In the present invention, the purity of the polyvinyl alcohol is preferably 99%. In the present invention, the water is preferably deionized water. In the present invention, the cobalt salt preferably includes cobalt nitrate; the iron salt preferably includes ferrous chloride; the manganese salt preferably includes manganese nitrate; and the copper salt preferably includes copper nitrate. In the present invention, the mass ratio of the polyvinyl alcohol to the transition metal element in the transition metal salt is preferably 0.2 to 2:1, and more preferably 0.5 to 1.5:1. The present invention has no special limitation on the amount of water, as long as the polyvinyl alcohol and the transition metal salt can be evenly dispersed.
[0090] In the present invention, the mixing preferably includes: dispersing polyvinyl alcohol in water, then adding a transition metal salt and continuing stirring; the dispersion is carried out under stirring conditions, the dispersion temperature is preferably 90°C, and the time is preferably 30 minutes; the continued stirring time is preferably 30 minutes.
[0091] The invention mixes multi-level pore ZSM-11 molecular sieve and water to obtain molecular sieve liquid.
[0092] In the present invention, the water is preferably deionized water. In the present invention, the mixing is preferably carried out under stirring, and the stirring time is preferably 15 minutes.
[0093] After obtaining the metal salt solution and the molecular sieve feed liquid, the present invention drips the molecular sieve feed liquid into the metal salt solution under stirring, continues stirring, and then calcines to obtain the molecular sieve catalyst.
[0094] In the present invention, the dripping rate is preferably 4 to 10 mL / min. In the present invention, the continued stirring time is preferably 4 hours. After the continued stirring, the present invention also preferably includes drying the obtained system, and the drying temperature is preferably 90°C. In the present invention, the calcination temperature is preferably 450 to 500°C, and the insulation time is preferably 6 to 12 hours.
[0095] The present invention also provides the use of the molecular sieve catalyst in the above technical solution in catalytic degradation of non-steroidal drugs or antibiotics. In the present invention, the degradation is preferably carried out in the presence of persulfate, and the persulfate preferably includes peroxymonosulfate.
[0096] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0097] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0098] Example 1
[0099] The catalyst of this embodiment is Co / Z11-PVA-1.5, and the mass ratio of PVA to Co during the catalyst synthesis process is 1.5.
[0100] (1) Synthesis of hierarchical ZSM-11 molecular sieve: 7.2652 g of tetrabutylammonium hydroxide solution (mass concentration of 25%, TBAOH) and 0.3176 g of sodium hydroxide (purity of 99%, NaOH) were added to 4.2406 g of deionized water in sequence, and stirred for 15 min. Then, 9.6781 g of silica sol (JN-40, solid content of 40%) was added thereto. After stirring at room temperature for 24 h, a molar ratio of TBAOH:SiO was obtained. 2 :H 2 O:NaOH=9:90:1065:12.897 gel system;
[0101] The obtained gel system was crystallized at a temperature of 85°C and a rotation speed of 15 rpm for 48 hours, then the temperature was raised to 120°C for further crystallization for 48 hours, and finally crystallized at 165°C for 24 hours; the obtained product was separated and dried by a centrifuge (5000 rpm) and then calcined at 600°C for 12 hours to remove the template agent, thereby obtaining the parent ZSM-11 molecular sieve;
[0102] 2 g of the above-mentioned parent ZSM-11 molecular sieve was dispersed in 20 mL of TBAOH solution (0.7 mol / L), stirred for 30 min, and then statically crystallized at 165 ° C for 72 h; the obtained product was separated by centrifuge (5000 rpm), dried, and calcined at 600 ° C for 12 h to remove the template agent, and then placed in 50 mL of 1 mol / L NH 4 Cl solution, exchanged in a water bath at 80 °C for 8 h, repeated for 3 times, and then the obtained sample was calcined at 600 °C for 6 h to obtain a hierarchical pore ZSM-11 molecular sieve.
[0103] (2) Preparation of Co / Z11-PVA-1.5 catalyst: 0.2224 g of polyvinyl alcohol (99% purity, PVA) was placed in 20 mL of deionized water, stirred at 90°C for 30 min, and then 0.7324 g of cobalt nitrate (99% purity, Co(NO 3 ) 2 6H 2 O), and then stirred for 30 min to obtain a metal salt solution;
[0104] Take 1g of multi-level pore ZSM-11 molecular sieve and disperse it in 10mL of deionized water, stir for 15min to obtain molecular sieve liquid;
[0105] The molecular sieve solution was slowly added dropwise into the metal salt solution at a rate of 10 mL / min. After stirring for 4 h, the sample was dried at 90°C and calcined at 500°C for 6 h to obtain the Co / Z11-PVA-1.5 molecular sieve catalyst.
[0106] Example 2
[0107] A molecular sieve catalyst was prepared in the manner of Example 1, wherein the amount of polyvinyl alcohol added was 0.0296 g. The obtained molecular sieve catalyst was recorded as Co / Z11-PVA-0.2.
[0108] Example 3
[0109] A molecular sieve catalyst was prepared in the manner of Example 1, wherein the amount of polyvinyl alcohol added was 0.1482 g. The obtained molecular sieve catalyst was recorded as Co / Z11-PVA-1.
[0110] Example 4
[0111] A molecular sieve catalyst was prepared in the manner of Example 1, wherein the amount of polyvinyl alcohol added was 0.2965 g. The obtained molecular sieve catalyst was recorded as Co / Z11-PVA-2.
[0112] Comparative Example 1
[0113] A molecular sieve catalyst was prepared in the manner of Example 1, without adding polyvinyl alcohol. The obtained catalyst was denoted as Co / Z11.
[0114] Performance Testing
[0115] Test Example 1
[0116] Figure 1 The XRD pattern of Co / Z11-PVA-1.5 obtained in Example 1 shows that the characteristic diffraction peaks at 37.0°, 45.5° and 65.5° of 2θ correspond to Co 3 O 4 (PDF: 78-1970) (311), (400) and (440) crystal planes, and the remaining diffraction peaks are characteristic diffraction peaks of the carrier ZSM-11 molecular sieve.
[0117] Figure 2 The FT-IR spectrum of Co / Z11-PVA-1.5 obtained in Example 1 shows that the wavelengths at 667 and 571 cm -1 The absorption peaks at 3 O 4 Co 3+ -O 2- and Co 2+ -O 2- The XRD and FT-IR results fully confirm that the Co species on the catalyst is Co 3 O 4 .
[0118] Figure 3 TEM image of Co / Z11-PVA-1.5 obtained in Example 1. Figure 3It can be seen from a that the intracrystalline mesopores run through the entire molecular sieve particle, which indicates that the ZSM-11 molecular sieve has a multi-level pore structure; HRTEM ( Figure 3 b) further confirmed that Co 3 O 4 The exposed crystal plane is (311) crystal plane; element mapping ( Figure 3 The cg) results showed that Co 3 O 4 The nanoparticles are evenly dispersed on the hierarchical ZSM-11 molecular sieve support, and the particle size distribution shows that Co 3 O 4 The average particle size is 2.4 nm.
[0119] Figure 4 N is the Co / Z11-PVA-1.5 obtained in Example 1 2 Adsorption-desorption isotherms show that at 0.7 <P / P 0 There is an obvious hysteresis loop in the range of <1.0, which corresponds to the capillary condensation in the intracrystalline mesopores.
[0120] Figure 5 This is the pore size distribution curve of Co / Z11-PVA-1.5 obtained in Example 1, which further confirms the existence of mesopores (about 11 nm in size) in Co / Z11-PVA-1.5.
[0121] Figure 6 The XPS full spectrum of the molecular sieve catalyst obtained in Examples 1 to 4 and Comparative Example 1 ( Figure 6 a) and high-resolution XPS spectra of Co 2p ( Figure 6 b), and quantitative analysis was performed using XPS data processing software Avantage. The results are shown in Table 1. It can be seen that the mass proportions of Co species in the external surface element composition of Co / Z11, Co / Z11-PVA-0.2, Co / Z11-PVA-1, Co / Z11-PVA-1.5 and Co / Z11-PVA-2 catalysts are 2.9%, 4.7%, 15.4%, 17.3% and 21.8%, respectively, indicating that the introduction of PVA helps to increase the distribution proportion of Co species on the external surface of the catalyst and improve the accessibility of metal active sites.
[0122] Table 1 Co species content, spatial distribution and valence distribution of molecular sieve catalysts
[0123] catalyst Co(bulk phase) Co(surface) <![CDATA[Co 2+ / (What 2+ +What 3+ )]]> Co / Z11 11.7% 2.9% 62.5% Co / Z11-PVA-0.2 11.9% 4.7% 64.1% Co / Z11-PVA-1 12.1% 15.4% 63.2% Co / Z11-PVA-1.5 11.8% 17.3% 64.8% Co / Z11-PVA-2 11.7% 21.8% 64.0%
[0124] The bulk content refers to the content of all Co elements in the molecular sieve catalyst.
[0125] Figure 7The high-resolution XPS fine spectra of Co 2p of the molecular sieve catalysts obtained in Examples 1 to 4 and Comparative Example 1, in which 796.3 eV and 781.2 eV are respectively attributed to Co 2+ Co 2p 1 / 2 and Co 2p 3 / 2 The characteristic absorption peaks of 794.7eV and 779.6eV are respectively attributed to Co 3+ Co 2p 1 / 2 and Co 2p 3 / 2 The results of peak fitting calculation are shown in Table 1. It can be seen that the Co in Co / Z11, Co / Z11-PVA-0.2, Co / Z11-PVA-1, Co / Z11-PVA-1.5 and Co / Z11-PVA-2 catalysts 2+ / (Co 2+ +Co 3+ ) are 62.5%, 64.1%, 63.2%, 64.8% and 64.0%, respectively, indicating that the introduction of PVA does not change the valence distribution of Co species.
[0126] Fig.14 TEM image of the molecular sieve catalyst obtained in Comparative Example 1. Fig.14 a and element mapping( Fig.14 From the cg) image, we can see that the active component Co 3 O 4 The nanoparticles are unevenly distributed on the multi-level porous ZSM-11 molecular sieve carrier, and there are large agglomerations; HRTEM ( Fig.14 b) further confirmed that Co 3 O 4 The exposed crystal plane is (311) and the particle size statistical distribution shows that Co 3 O 4 The average particle size is 29 nm.
[0127] Test Example 2
[0128] Testing the performance of the molecular sieve catalysts obtained in Examples 1 to 4 and Comparative Example 1 in activating peroxymonosulfate to catalyze the degradation of acetaminophen;
[0129] The specific operation is: weigh 100g of acetaminophen solution (20ppm) and place it in a 250mL beaker, add 50mg of molecular sieve catalyst and ultrasonicate for 20min to achieve the adsorption-desorption equilibrium of acetaminophen on the catalyst. During this period, 1mL is sampled with a pipette every 10min and placed in a 5mL centrifuge tube. Then, 50mg of potassium permonosulfate is added to the above system to start the catalytic degradation reaction, and 1mL is sampled at a specific reaction time (5, 10, 15, 20, 30, 40, 50, 60min) and placed in a 5mL centrifuge tube. At the same time, 1mL of methanol is quickly added to quench the reaction. After filtering through a 0.22μm polyethersulfone filter membrane, it is analyzed by high performance liquid chromatography (HPLC). The catalytic degradation effect is as follows Figure 8 As shown. Among them, Figure 8 The a is C t / C 0 The graph of reaction time changes, Figure 8 b is ln(C t / C 0 ) versus reaction time;
[0130] from Figure 8 As can be seen from a, as the PVA / Co molar ratio increases from 0.2 to 1.5, the degradation rate of acetaminophen gradually accelerates, and further increasing the PVA / Co molar ratio to 2, the degradation rate of acetaminophen decreases slightly. Figure 8 As shown in b, the rate constant k value of Co / Z11-PVA-1.5 catalyst is the largest, which is 0.365min -1 Therefore, the Co / Z11-PVA-1.5 catalyst has the best degradation performance for acetaminophen.
[0131] Using Co / Z11 as catalyst, acetaminophen was degraded by only 32.2% within 60 min, and the degradation rate constant was only 0.006 min. -1 , it can be seen that the catalytic activity of Co / Z11 is poor. In contrast, the degradation rate constant of acetaminophen for the optimal catalyst Z11-PVA-1.5 (0.365min -1 ) is 60 times higher than that of Co / Z11 catalyst.
[0132] Test Example 3
[0133] Taking the molecular sieve catalyst obtained in Example 1 as an example, the effect of different catalyst contents on the catalytic degradation of acetaminophen by activated peroxymonosulfate was verified;
[0134] The specific operation is shown in Test Example 2, where the mass of the catalyst is 10, 20, 30, 40, and 50 mg respectively; the catalytic degradation effect is as follows Fig. 9 As shown, Fig. 9 The a is Ct / C 0 The graph of reaction time changes, Fig. 9 b is ln(C t / C 0 ) versus reaction time;
[0135] from Fig. 9 It can be seen that increasing the catalyst mass from 10 mg to 50 mg, the degradation rate of acetaminophen increased from 0.023 min -1 Increased to 0.365min -1 However, too much catalyst feeding will increase the degradation cost, so the preferred catalyst mass is 50 mg.
[0136] Test Example 4
[0137] Taking the molecular sieve catalyst obtained in Example 1 as an example, the effect of different acetaminophen solution concentrations on the catalytic degradation of acetaminophen by activated peroxymonosulfate was verified;
[0138] For specific operations, see Test Example 2, where the concentrations of the acetaminophen solution are 20, 25, 30, and 40 ppm respectively; the catalytic degradation effect is as follows Fig.10 As shown;
[0139] from Fig.10 It can be seen that the higher the acetaminophen concentration, the greater the residual acetaminophen concentration in the degradation system after 60 minutes of reaction, that is, the greater the degree of incomplete degradation. This shows that more catalyst mass is required to achieve complete degradation in a high-concentration acetaminophen degradation system.
[0140] Test Example 5
[0141] Taking the molecular sieve catalyst obtained in Example 1 as an example, the effect of different initial pH values of acetaminophen solution on the catalytic degradation of acetaminophen by activated peroxymonosulfate was verified;
[0142] The specific operation is shown in Test Example 2, wherein after adding the catalyst, the reaction solution is adjusted to have different initial pH values using 1 mol / L sulfuric acid or sodium hydroxide solution, and the initial pH values are 3, 4.6, 6.0, 7.1, 8.2, and 9.3, respectively; the catalytic degradation effect is as follows Fig.11 As shown;
[0143] from Fig.11 It can be seen that although increasing or decreasing the initial pH value of the reaction solution slows down the degradation rate of acetaminophen, as long as the initial pH value of the reaction solution is between 3 and 9, acetaminophen can still be degraded by more than 98% within 60 minutes. Therefore, the catalyst has good resistance to the influence of the acidity and alkalinity of the reaction solution. This result also shows that the optimal initial pH of the reaction solution is near neutral.
[0144] Test Example 6
[0145] Various anions and cations are widely present in natural water bodies, and the concentration is usually around 30 ppm, which may affect the degradation performance of the catalyst; taking the molecular sieve catalyst obtained in Example 1 as an example, the effect of different anions and cations on the catalytic degradation of acetaminophen by activated peroxymonosulfate was verified;
[0146] The specific operation is shown in Test Example 2, wherein a certain amount of Na 2 SO 4 , K 2 SO 4 、CaSO 4 MgSO 4 、KNO 3 , KH 2 PO 4 , KHCO 3 , so that Na + , K + , Ca 2+ Mg 2+ 、NO 3- , H 2 PO 4 - , HCO 3 - The concentration is 50ppm; the catalytic degradation effect is as follows Fig.12 As shown;
[0147] from Fig.12 It can be seen that after adding different types of anions and cations, the degradation rate of acetaminophen decreased slightly, but it could still be completely degraded within 40 minutes of reaction. Therefore, the catalyst has a strong ability to resist the interference of anions and cations in water.
[0148] Test Example 7
[0149] Taking the molecular sieve catalyst obtained in Example 1 as an example, the performance of activated peroxymonosulfate in catalyzing the degradation of antibiotics was verified;
[0150] For specific operations, see Test Example 2, in which the acetaminophen solution is replaced with different types of quinolone antibiotic solutions (20 or 50 ppm), including ciprofloxacin, norfloxacin, ofloxacin, etc.; the catalytic degradation effect is as follows Fig.13 As shown;
[0151] from Fig.13It can be seen that 20ppm of ciprofloxacin, norfloxacin and ofloxacin can be completely degraded within 15min; increasing the substrate concentration to 50ppm, the degradation rate of the three antibiotics slightly decreased, but they can still be completely degraded within 40min. Therefore, the catalyst is not only suitable for the degradation of non-steroidal drugs, but also for the degradation of antibiotics, and has good substrate applicability.
[0152] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a multi-level pore ZSM-11 molecular sieve, characterized in that: The following steps are involved: first mixing tetrabutylammonium hydroxide solution, sodium hydroxide, silica sol and water to obtain a gel system; The gel system is subjected to dynamic crystallization and first calcination in sequence to obtain a parent ZSM-11 molecular sieve; The parent ZSM-11 molecular sieve and the tetrabutylammonium hydroxide solution are mixed for the second time to obtain a dispersed system; The dispersed system is sequentially subjected to static crystallization and secondary calcination to obtain a primary ZSM-11 molecular sieve; The primary ZSM-11 molecular sieve is placed in an ammonium chloride solution for ion exchange and then subjected to a third calcination to obtain the multi-level pore ZSM-11 molecular sieve.
2. The preparation method according to claim 1, characterized in that: In the first mixing, the mass concentration of the tetrabutylammonium hydroxide solution is 10-25%; The solid content of the silica sol is 25-40%; The molar ratio of tetrabutylammonium hydroxide in the tetrabutylammonium hydroxide solution, silicon dioxide in the silica sol, water and sodium hydroxide is 4.5-18:60-180:810-2250:9-18; The first mixing is performed under stirring conditions, the stirring temperature is room temperature, and the time is 18 to 30 hours.
3. The preparation method according to claim 1, characterized in that: The dynamic crystallization is carried out under rotation, and the rotation number is 10-20 rpm. The dynamic crystallization includes sequentially performing first stage crystallization, second stage crystallization and third stage crystallization; The temperature of the first stage crystallization is 70-90°C and the time is 36-72h; The temperature of the second stage crystallization is 110-130°C and the time is 36-72h; The temperature of the third stage crystallization is 150-170°C and the time is 20-36h; The temperature of the first calcination is 570-600° C., and the heat preservation time is 12-18 hours.
4. The preparation method according to claim 1, characterized in that: In the second mixing, the concentration of the tetrabutylammonium hydroxide solution is 0.40 to 1.4 mol / L; The dosage ratio of the parent ZSM-11 molecular sieve and the tetrabutylammonium hydroxide solution is 1g: 10-25mL; The second mixing is performed under stirring conditions, and the stirring time is 30 to 120 minutes.
5. The preparation method according to claim 1, characterized in that: The static crystallization temperature is 150-180°C and the time is 36-72h; The second calcination temperature is 570-600°C, and the holding time is 12-18h; The ion exchange temperature is 60-80°C, the time is 8-12h, and it is repeated 3 times; The temperature of the third calcination is 570-600° C., and the heat preservation time is 6-12 hours.
6. The multi-level pore ZSM-11 molecular sieve prepared by the preparation method according to any one of claims 1 to 5.
7. A molecular sieve catalyst, characterized in that: It includes a multi-level pore ZSM-11 molecular sieve and a transition metal oxide loaded on the multi-level pore ZSM-11 molecular sieve; The multi-level pore ZSM-11 molecular sieve is the multi-level pore ZSM-11 molecular sieve according to claim 6; The transition metal oxide includes Co3O4, Fe3O4, Mn3O4 or CuO.
8. The molecular sieve catalyst according to claim 7, characterized in that: The loading mass percentage of the transition metal oxide is 10-15%; The average particle size of the transition metal oxide is 2 to 3.5 nm.
9. The method for preparing the molecular sieve catalyst according to claim 7 or 8, characterized in that: The following steps are involved: Mixing polyvinyl alcohol, a transition metal salt and water to obtain a metal salt solution; the transition metal salt includes a cobalt salt, an iron salt, a manganese salt or a copper salt; Mixing the multi-level pore ZSM-11 molecular sieve and water to obtain a molecular sieve feed solution; Under stirring conditions, the molecular sieve material liquid is dropped into the metal salt solution, and after continuing to stir, calcination is performed to obtain the molecular sieve catalyst.
10. Use of the molecular sieve catalyst according to claim 7 or 8 or the molecular sieve catalyst prepared by the preparation method according to claim 9 in catalytic degradation of non-steroidal drugs or antibiotics.